Beliefs of secondary school teachers towards education for sustainable development: a statistical research - Sijo Varghese; P. M. Mathew (International Journal of Evaluation and Research in Education (IJERE), 2026)
Educators are the architects of sustainable development (SD), transforming society and balancing development and sustainability. They enhance education for sustainable development (ESD) and societal transformation, driving innovative evolution and future-oriented development within the community. ESD, a millennium, and sustainable development goal (SDG), need to be implemented globally. Teachers are vital in transmitting knowledge, beliefs, and skills required for sustainability in the changing environment. This study examined secondary school teachers’ beliefs about ESD based on their professional qualifications, teaching experience, and position. The authors used a survey approach and collected the data using a belief assessment tool, i.e., the ESD beliefs scale. The respondents were 400 secondary school teachers in Kerala, India. The study used an item-based evaluation to achieve these objectives and calculated t-values, F-values, and percentages. The research findings indicated that teachers hold constructive opinions towards ESD. The positional status of teachers did not alter beliefs regarding ESD among secondary school teachers. In contrast, professional qualifications and years of teaching experience significantly influenced these ESD beliefs. The findings from this study enable education stakeholders to amend the current secondary education system for SD.